(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Indu Sundaresan is one of the emerging Indian woman novelists. Her love for India has forced her to rewrite the erased history of Indian emperors and Queens. The Mountain of Light is a brilliant novel that highlights the excellent qualities of Indian rulers. She focuses on the life-oriented culture of India which stands in sharp contrast with that of Occidental culture. The family system, the genuine love of husband and wife, the loyalty of friends and the bravery of Indian king Ranjith Singh and his wife to retain their power over the Indian territory is passionately recounted in the novel.